Revealing a Phenotypical Appearance of Ibrutinib Resistance in Patients With Chronic Lymphocytic Leukaemia by Flow Cytometry - Ferenc Takács; Ferenc Takács; Lili Kotmayer; Ágnes Czeti; Gábor Szalóki; Tamás László; Gábor Mikala; Ágnes Márk; András Masszi; Péter Farkas; Márk Plander; Júlia Weisinger; et al. (Frontiers Media S.A., 2022)
Background: Ibrutinib is widely known as an effective and well-tolerated therapeutical choice of the chronic lymphocytic leukaemia (CLL). However, acquired resistance may occur during the treatment, causing relapse. Early detection of ibrutinib resistance is an important issue, therefore we aimed to find phenotypic markers on CLL cells the expression of which may correlate with the appearance of ibrutinib resistance.Methods: We examined 28 patients' peripheral blood (PB) samples (treatment naïve, ibrutinib sensitive, clinically ibrutinib resistant). The surface markers' expression (CD27, CD69, CD86, CD184, CD185) were measured by flow cytometry. Furthermore, the BTKC481S resistance mutation was assessed by digital droplet PCR. Moreover, the CLL cells' phenotype of a patient with acquired ibrutinib resistance was observed during the ibrutinib treatment.Results: The expression of CD27 (p = 0.030) and CD86 (p = 0.031) became higher in the clinically resistant cohort than in the ibrutinib sensitive cohort. Besides, we found that high CD86 and CD27 expressions were accompanied by BTKC481S mutation. Our prospective study showed that the increase of the expression of CD27, CD69 and CD86 was noticed ahead of the clinical resistance with 3 months.Conclusion: Our study suggests that the changes of the expression of these markers could indicate ibrutinib resistance and the examination of these phenotypic changes may become a part of the patients' follow-up in the future.